Hubungan antara Efikasi Diri dengan Kecemasan Akademik di Kalangan Siswa SMK Pratama Widya Mandala Tahun 2026 - Afdinal Irham Yudiputra Maksudi; I Wayan Susante; Made Wery Dartiningsih (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aimed to determine the relationship between self-efficacy and academic anxiety among students of SMK Pratama Widya Mandala in 2026. This research employed a quantitative approach with a correlational research design. The sample consisted of 90 eleventh-grade students of SMK Pratama Widya Mandala. The research instruments were self-efficacy and academic anxiety questionnaires that had met the validity and reliability requirements. Data were analyzed using the Pearson Product-Moment Correlation technique with the assistance of IBM SPSS Statistics version 25. The results showed a significant negative relationship between self-efficacy and academic anxiety, with a correlation coefficient of r = 0.832 and a significance value of p < 0.001. These findings indicate that the higher the students' self-efficacy, the lower their academic anxiety. Self-efficacy contributed 69.22% to students' academic anxiety, while the remaining 30.78% was influenced by other factors outside the scope of this study. These findings suggest that self-efficacy is an important factor in reducing students' academic anxiety.